2006
DOI: 10.1177/0010414005284374
|View full text |Cite
|
Sign up to set email alerts
|

Does Proportional Representation Foster Closer Congruence Between Citizens and Policy Makers?

Abstract: This article assesses the claim that proportional representation (PR) fosters a closer correspondence between the views of citizens and the positions of the government. The study uses the Comparative Study of Electoral Systems data set and compares respondents’ self-placements on a Left-Right scale with placements of cabinet parties’ locations in 31 election studies. The authors argue that PR has two contradictory consequences. On one hand, PR leads to more parties and more choice for voters; but these parties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
201
2
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 244 publications
(218 citation statements)
references
References 29 publications
6
201
2
9
Order By: Relevance
“…Early work by Hotelling (1929) and Downs (1957) demonstrated that if voters vote for the closest (in policy and/or spatial terms) candidate in a majoritarian election with only two candidates the latter two should position themselves at the location of the consider a closer look at the exact "mechanics" linking voters to political actors (e..g, MPs, parties, governments) as proposed by Blais and Bodet (2006) necessary. During the time when Israel elected its prime-minister in a direct election, any measure of congurence involving the government would have a different meaning than during the time when parliament selected the prime-minister.…”
Section: Electoral Systems Incentives and Representationmentioning
confidence: 99%
See 4 more Smart Citations
“…Early work by Hotelling (1929) and Downs (1957) demonstrated that if voters vote for the closest (in policy and/or spatial terms) candidate in a majoritarian election with only two candidates the latter two should position themselves at the location of the consider a closer look at the exact "mechanics" linking voters to political actors (e..g, MPs, parties, governments) as proposed by Blais and Bodet (2006) necessary. During the time when Israel elected its prime-minister in a direct election, any measure of congurence involving the government would have a different meaning than during the time when parliament selected the prime-minister.…”
Section: Electoral Systems Incentives and Representationmentioning
confidence: 99%
“…In a series of recent articles (e.g. Dow, 2001; Blais and Bodet, 2006;Ezrow, 2007;Ezrow, 2008;Warwick, 2009;Golder and Stramski, 2010;Powell, 2010) a debate has emerged on how congruence between citizens and their representatives (MPs, parties, and governments) should be measured and whether and how this congruence depends on the electoral system.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations